A low-power metal–oxide scan driver circuit outputting non-overlapping pulses with DC power-supplied buffer - HyeongMin Kim; JungSuk Oh; YiKyoung You; SangWoon Lee; KeeChan Park (Journal of Information Display)
This paper proposes a novel metal–oxide (MOx) thin-film transistors (TFT)-based scan driver circuit with a DC power-supplied buffer. This circuit has two parts: a ‘carry generation block (CGB)’ and an ‘output generation block (OGB).’ The CGB generates a carry pulse by the bootstrapping effect of pull-up TFT with the aid of clock signal; clock-supplied bootstrapping. Then the OGB is controlled by the carry pulse, and the output pulse is generated by the bootstrapping effect of pull-up buffer TFT with DC power supply; DC-supplied bootstrapping. In the proposed circuit, the pull-up TFT in CGB does not need to have wide dimensions because the carry signal is separated from the large capacitive load in the pixel area. Accordingly, the capacitive load of the clock signal is significantly reduced, and the dynamic power consumption associated with clock toggling decreases remarkably compared with the conventional scan driver circuit that uses the clock-supplied bootstrapping for the wide output buffer TFT. In addition, a bootstrapping inverter in OGB makes the output pulse width the same as the clock-high duration, preventing the output pulses from overlapping, which is required for most of the organic light-emitting diode (OLED) pixel circuits with in-pixel compensation.